Evidence of a target resistance to antivitamin K rodenticides in the roof rat Rattus rattus: identification and characterisation of a novel Y25F mutation in the Vkorc1 gene. Issue 3 (26th May 2015) - Goulois, Joffrey; Chapuzet, Audrey; Lambert, Véronique; Chatron, Nolan; Tchertanov, Luba; Legros, Lionel; Benoît, Etienne; Lattard, Virginie
Abstract: BACKGROUND: In spite of intensive use of bromadiolone, rodent control was inefficient on a farm infested by rats in Zaragoza, Spain. While metabolic resistance was previously described in this rodent species, the observation of a target resistance to antivitamin K rodenticides had been poorly documented in Rattus rattus . RESULTS: From rats trapped on the farm, cytochrome b and Vkorc1 genes were amplified by PCR and sequenced in order to identify species and detect potential Vkorc1 mutations. VKORC1‐deduced amino acid sequences were thus expressed in Pichia pastoris, and inhibition constants towards various rodenticides were determined. The ten rats trapped on the farm were all identified as R. rattus . They were found to be homozygous for the g.74A>T nucleotide replacement in exon 1 of the Vkorc1 gene, leading to p.Y25F mutation. This mutation led to increased apparent inhibition constants towards various rodenticides, probably caused by a partial loss of helical structure of TM4. CONCLUSION: The p.Y25F mutation detected in the Vkorc1 gene in R. rattus trapped on the Spanish farm is associated with the resistance phenotype to bromadiolone that has been observed. It is the first evidence of target resistance to antivitamin K anticoagulants in R. rattus . © 2015 Society of Chemical Industry